2012
DOI: 10.1590/s0074-02762012000100018
|View full text |Cite
|
Sign up to set email alerts
|

Pfcrt haplotypes and the evolutionary history of chloroquine-resistant Plasmodium falciparum

Abstract: Mutations in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 56 publications
4
49
1
Order By: Relevance
“…Plasmodium vivax resistance to CQ is rampant in some regions of Southeast Asia [2,3] and Western Pacific [4], while the emergence of CQ resistance within other regions of the world, including Central and South America [5-7], Southern Asia [8] and even the Indian Subcontinent [9-13] is less evident and represented in the literature mainly in the form of medical case reports. Similar to other countries (reviewed in [14]), CQ resistant Plasmodium falciparum emerged in India in the 1970s [15,16]. Decades of research have linked P. falciparum drug resistance with a variety of single nucleotide polymorphisms (SNPs) causing non-synonymous amino acid substitutions in the P. falciparum CQ resistance transporter gene ( Pfcrt ) [17] and copy number variation in the P. falciparum multidrug resistance gene 1 ( Pfmdr1 ) [18].…”
Section: Introductionmentioning
confidence: 77%
“…Plasmodium vivax resistance to CQ is rampant in some regions of Southeast Asia [2,3] and Western Pacific [4], while the emergence of CQ resistance within other regions of the world, including Central and South America [5-7], Southern Asia [8] and even the Indian Subcontinent [9-13] is less evident and represented in the literature mainly in the form of medical case reports. Similar to other countries (reviewed in [14]), CQ resistant Plasmodium falciparum emerged in India in the 1970s [15,16]. Decades of research have linked P. falciparum drug resistance with a variety of single nucleotide polymorphisms (SNPs) causing non-synonymous amino acid substitutions in the P. falciparum CQ resistance transporter gene ( Pfcrt ) [17] and copy number variation in the P. falciparum multidrug resistance gene 1 ( Pfmdr1 ) [18].…”
Section: Introductionmentioning
confidence: 77%
“…The first report describing the prevalence of polymorphisms in Pfcrt conferring CQR showed that all the P. falciparum isolates were carrying the Pfcrt mutant alleles [2, 5]. The Pfcrt CVIET haplotype has been shown to be the most prevalent in Africa in contrast to the SVMNT haplotype found predominantly in Southeast Asia [23, 26]. Also, the occurrence of the Pfcrt M74I and N75E mutations has been linked to the K76T mutation as reported by Severini et al who noted a 100% linkage between these alleles [27].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of two distinct pfcrt genotype, CV IET (89%) and S VMN T (4%) suggests that CQR in Yemen has evolved from at least two different origins. Globally, there are five genotypes of pfcrt CV IET , S VMN T , S V IET , CVMN T and CV T N T [47]. The CV IET genotype is predominant in Africa [48], while the S VMN T is common in Asian countries close to the Arabian Peninsula, such as Iran [43], India [49] and Pakistan [41,42].…”
Section: Discussionmentioning
confidence: 99%